Brand strategy for 103 FM radio station - Thus Sang-urai; Levermore, Roger; Badir, Yuosre F. M.; Ransom, Lakeesha K.; Royal Thai Government; Asian Institute of Technology Fellowships (Pathum Thani, Thailand : Asian Institute of Technology, 2020)
Within the digitally disrupted age in the radio industry, 103 Like FM, a Thai easylistening radio station, is facing challenges from both competitors and the switching audience behavior towards music streaming services. Regarding these challenges, the company needs to reach out and gain more audience to survive in the current situation even though they already provided their service through online platforms such as website and application. Competitive analysis shows that easy-listening radio stations share close target, positioning, communication and brand image and those stations that have been in this market for a long time have a greater advantage in gaining larger audience base that know them before. Moreover, the name concept of 2103 like FM3 came from the emergence of social media activities and its unique selling point is the freedom to let listeners express their emotion online but when social media has become a major part of everyday lives, the core identity of 103 like FM now can be claimed by other stations as well. The company is now having problem building its recognition and awareness from the audience in the radio market due to its weak brand positioning and identity. There is an opportunity for 103 Like FM to react to the 2Joy of Missing out3 consumer trend where consumers seek relaxation and disconnection and position itself as radio to forget the stress since easy-listening songs give the sense of relaxation and calmness. They can differentiate themselves by focusing on how to reduce stress, how to improve well-being, or how to fall asleep better in an 2overconnected3 life, listeners are looking for relaxing programs, meditation assistance, or chill out music that helps with rest and disconnection. New brand identity and brand positioning are reconsidered according to this trend. These qualities are then reflected and expressed through brand visual and verbal identity which are logo and tagline. Brand awareness strategy is considered for the station to reach out to a wider group of audience through content marketing and customer relationship management (CRM). A prototype of a CRM application is developed to suggest some guidelines for further improvement.
An Intern Project submitted in partial fulfillment of the requirements for the degree of Master of Business Administration
Intern Project (M.B.A.) - Asian Institute of Technology, 2020
Keywords: Branding (Marketing) -- Thailand; Radio stations -- Thailand